Does Surgical-site Multimodal Drug Injection After Palmar Plating of Distal Radius Fractures Improve Pain Scores? - Jung, Hyoung-Seok (Clin Orthop Relat Res, 2020)
BACKGROUND: Although palmar locked plating is a stable fixation method frequently used to treat unstable distal radius fractures (DRFs), surgical treatment may be painful, and so interventions to decrease that pain might improve our patients’ experiences with surgery. Some surgeons use local multimodal drug injections to decrease postoperative pain after lower-extremity arthroplasty, but little is known about the effectiveness of a local multimodal drug injection in patients who undergo palmar plating for DRFs. QUESTIONS/PURPOSES: (1) Do patients who receive a local multimodal drug injection after palmar plating for unstable DRFs have better pain scores at 4, 8, 24, and 48 hours after surgery than patients who have not received such an injection? (2) Do patients who receive a local multimodal drug injection have lower fentanyl consumption and administration of anti-emetic drugs within the first 48 hours after surgery than patients who have not received such an injection? METHODS: A randomized controlled study was performed between August 2018 and August 2019 at a single tertiary care referral center. Patients who underwent palmar plating for DRFs under general anesthesia were eligible for inclusion. Patients were allocated into two groups: Those who received a local multimodal drug injection, and those who did not receive an injection. During the study period, 101 patients treated with palmar plating for DRFs met the inclusion criteria and were enrolled and randomized. Fifty-two patients were allocated to the multimodal injection group and 49 were allocated to the control group. Three patients (two in the multimodal injection group and one in the control group) were excluded after randomization because their pain level was not registered at any timepoint and so they could not be analyzed; our analysis was by intention to treat, and there was no crossover. After palmar plating, patients in the multimodal injection group received an injection of ropivacaine (10 mL), morphine (5 mL), ceftezole (5 mL) as well as normal saline (5 mL) to the periosteal area, pronator quadratus muscle, subcutaneous area, and skin. There were no differences between the groups in terms of age (62 years ± 13 years in the multimodal injection group versus 62 years ± 11 years in the control group; p = 0.93), gender (84% [42 of 50] women in the multimodal injection group versus 77% [37 of 48] women in the control group; p = 0.39), hand dominance (70% [35 of 50] dominant wrist in the multimodal injection group versus 60% [29 of 48] dominant wrist in the control group; p = 0.32) and AO/Orthopaedic Trauma Association (AO/OTA) classification (p = 0.57). All patients underwent treatment with the same perioperative protocol, and 25 μg of fentanyl was injected intravenously when a patient complained of pain and asked for additional pain control after surgery. In addition, when a patient complained of nausea or vomiting associated with fentanyl use, an anti-emetic drug was also injected. All nursing staff who administered the analgesics and anti-emetic drugs were blinded to treatment allocation. These two groups were compared regarding their pain level using a 100-mm VAS at 4, 8, 24, and 48 hours postoperatively. The minimum clinically important difference (MCID) for the VAS score was set to 20 mm. VAS scores were also collected by nursing staff who remained blinded to the treatment allocation. The total amount of fentanyl use and the number of patients who received anti-emetic drugs associated with administration of fentanyl within the first 48 hours were also recorded. RESULTS: With an MCID of 20 points, we found no clinically important reduction in VAS scores among patients who received a local multimodal injection compared with those who did not receive an injection at 4 hours (34 ± 15 versus 41 ± 20, mean difference -7.079 [95% CI -13.986 to -0.173]; p = 0.045), 8 hours (27 ± 16 versus 40 ± 19, mean difference -12.263 [95% CI -19.174 to -5.353]; p = 0.001), 24 hours (18 ± 12 versus 29 ± 20, mean difference -11.042 [95% CI -17.664 to -4.419]; p = 0.001), and 48 hours (9 ± 8 versus 10 ± 6, mean difference -1.318 [95% CI -4.000 to 1.365]; p = 0.33). Within the first 48 hours after surgery, fentanyl consumption was lower in patients receiving a local multimodal injection than in control patients (25 μg [range 0-100 μg] versus 37.5 μg [range 0-125 μg], difference of medians -12.5; p = 0.01). There was also a difference between the study groups in terms of the proportion of patients who received anti-emetic medications (16% [8 of 50] in the multimodal injection group versus 35% [17 of 48] in the control group, odds ratio = 2.879 [95% CI 1.102 to 7.519]; p = 0.03). CONCLUSIONS: Our data suggest that patients who received a surgical-site multimodal analgesic injection after palmar plating for a distal radius fracture had no clinically important reduction in pain scores, but they did consume lower doses of opioid analgesics and fewer of these patients received anti-emetic drugs within 2 days of surgery. The high-potency opioids or other analgesia usually used for postoperative pain management have many side effects. Thus, reducing additional analgesia is as important as postoperative pain management and a surgical-site multimodal analgesic injection is one of the methods to achieve this a goal. LEVEL OF EVIDENCE: Level I, therapeutic study.